Permissioned blockchain based public procurement system. (December 2020) - Deshpande, J J; Gowda, M; Dixit, M; Khubbar, M S; Jayasri, B S; Lokesh, S
Abstract: Hundreds of public procurement projects are undertaken every day all over the country. The tenders for these projects are given to the winning contractor in an auction-like setting which have massive security issues. After a contractor wins a tender, the specifics of the progress of the work done are rarely properly monitored. The details of the finances spent on the project can be easily manipulated. To enable integrity, non-repudiation and immutability to the data requires the desirable technology to support the above requirements. Hence, the proposed system uses blockchain technology to provide transparency and trust to all parties involved in the network. The entire system consists of two modules such as the Tender Bidding system and Tender Monitoring system using a multi-organization blockchain network in the Hyperledger Fabric. The whole bidding process is improved by creating a decentralized descending auction system that will carry it out fairly and transparently. The Tender Monitoring system employs a custom endorsement policy to attain 100% consensus for attesting every transaction made regarding the progress of the project so that vital steps are ratified and recorded with evidence supporting their integrity. The main aspects of the system, its many components, deployment and drawbacks are viewed.